2012
DOI: 10.1007/s00192-012-1837-5
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle tenderness in asymptomatic, nulliparous women: topographical distribution and reliability of a visual analogue scale

Abstract: Pain upon palpation of the pelvic floor muscle in asymptomatic, nulliparous women should be considered an uncommon finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…For example, if the stiffness value was set at 462 N/m (mean of scale category 0: representing a “normal” muscle stiffness), participants assigned the stiffness value to anywhere between category −2 to +3 on the scale. Previous studies looking at repeatability of palpation scales in vivo have shown poor to moderate agreements, indicating the subjective nature of palpation …”
Section: Discussionmentioning
confidence: 95%
“…For example, if the stiffness value was set at 462 N/m (mean of scale category 0: representing a “normal” muscle stiffness), participants assigned the stiffness value to anywhere between category −2 to +3 on the scale. Previous studies looking at repeatability of palpation scales in vivo have shown poor to moderate agreements, indicating the subjective nature of palpation …”
Section: Discussionmentioning
confidence: 95%
“…However, the responsiveness, reliability and validity of vaginal palpation for measurement of activation of the PFM have been challenged [23]. Kavvadias et al [24], investigating PFM tenderness of healthy nulliparous young women, found poor reliability while Reissing et al [9] found that palpation had almost perfect correspondence in discriminating between PVD and healthy controls. Our study showed no significant differences in sEMG between women with PVD and controls in resting or peak activity.…”
Section: Discussionmentioning
confidence: 99%
“…FN31 Varying reliability has been found from pelvic floor muscle (PFM) studies assessing pain and tension using digital palpation scales. [73][74][75][76] Patients who present with alteration in the musculoskeletal structure need to be referred to a Physical Therapist well trained in the treatment of CPPS. FN32 Muscle tone is evaluated clinically as the resistance provided by a muscle when a pressure/deformation or a stretch is applied to it 46,77,78 Muscle tone may be altered in the presence or absence of pain.…”
Section: Musculoskeletalmentioning
confidence: 99%
“…Varying reliability has been found from pelvic floor muscle (PFM) studies assessing pain and tension using digital palpation scales …”
mentioning
confidence: 99%